Antibacterial Activities of Pentaclethra Macrophylla and Syzygium Samarangense against Opportunistic Bacteria Pathogens - Oluwanifise, OYEJIDE Stephen; Obinna, NWINYI; Ikhiwili, ONIHA Margaret; Joseph, OLUGBUYIRO; Olugbenga, TAIWO (International Journal of Advances in Life Science and Technology, 2022)
In this study, Pentaclethra macrophylla and Syzygium samarangense leaves was tested for their antibacterial activities against selected opportunistic bacterial strains. The crude extracts of the plants were extracted using methanol and fractionated into hexane, ethyl acetate and aqueous fractions. The antibacterial activity of the leaves against B. subtilis (ATCC® 6633™), S. aureus (ATCC® 25923™), E. coli (ATCC® 25922™), P. aeruginosa (ATCC® 9027™) was performed using the agar well diffusion technique at 20mg/ml extracts fractions. All plants extracts extract exhibited some antibacterial activity against at least one bacterial strain. P. macrophylla exhibited the highest inhibition against E. coli (25mm) compared to B. subtilis, S. aureus and P. aeruginosa. Similar observation was noted for S. samarangense where the highest inhibition was against E. coli (22mm). In conclusion, P. macrophylla and S. samaragense exhibited antibacterial activities against the selected bacteria. The ethyl acetate and aqueous extracts of both plants had the highest antibacterial activities. This indicates that P. macrophylla and S. samrangense leaves could be a source of antibacterial agent in overcoming antibacterial drug resistance.